Recovery of woody but not herbaceous native flora 10 years post old‐field restoration. Issue 3 (3rd September 2021) - Parkhurst, Tina; Prober, Suzanne M.; Standish, Rachel J.
Abstract: Vegetation recovery in old fields towards mature reference states is often limited by abiotic and biotic thresholds resulting from agricultural land use legacies, as commonly highlighted using state and transition models. Old‐field restoration may include interventions (e.g. planting of vegetation) to overcome these thresholds and assist transition between states. However, our understanding of the effectiveness of these interventions is limited. Using a point‐intercept transect method, we surveyed nine sites, each comprising a triplet of fallow cropland, planted old field and woodland reference plots to reflect states of old‐field restoration, from the degraded state to the reference state. We compared ground cover attributes, and richness and cover of woody and herbaceous flora species, using ANOVA and multivariate analyses. We found that a decade after planting, cover of leaf litter and woody debris in planted old fields were significantly higher than in the fallow croplands; however, woodland reference conditions were not achieved. Cover of logs was similar to the fallow cropland. Woody species cover and richness were similar in planted old fields and woodland reference plots, with planted old fields having more than 60% of the shrub species richness and cover, and similar tree species richness, to the woodland reference plot. In contrast, whilst herbaceous species contributed more than half the plant species richness in reference woodland plots, there were significantly fewer herbaceous species in the planted old fields, which were more similar to the fallow croplands. Cover of exotic annual forbs in planted old fields was about half that of fallow cropland, and exotic annual grass cover was similar to the reference woodland. Our results show that active restoration of old fields increased leaf litter, woody debris and cover and richness of trees and perennial shrubs. However, native herbaceous species richness, and to some extent cover, remained similar to the fallow cropland. To effect transitioning of the herbaceous layer to the woodland reference state, further intervention such as removal of exotics, followed by sowing or planting native herbaceous species, may be necessary. Abstract : Ecological restoration in agricultural landscapes is often limited by abiotic and biotic barriers. Active restoration of old fields achieves recovery of woody plant species through planting and volunteer shrub establishment within a decade. However, herbaceous species did not establish, requiring further research to test intervention that enable establishment.